2020
DOI: 10.1055/s-0040-1721011
|View full text |Cite
|
Sign up to set email alerts
|

Unmet Needs for Transdermal Patch Management in Electronic Medication Administration Records: An Analysis of Data from 66 Aged Care Facilities

Abstract: Background Transdermal medication patches have caused serious adverse events in residential aged care facilities (RACFs). Preliminary research suggests that facilities are using a workaround consisting of manually entered reminders in their electronic medication administration records (eMARs) to prompt staff to check and remove patches, because the eMAR does not support these tasks. However, the prevalence and factors associated with use of this workaround among facilities is unknown. Objectives The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…One RCT was included, 22 and the remaining studies were observational. Of 22 observational studies, 18 reported the cross‐sectional prevalence of opioid use across various assessment periods 8,23–39 . One study combined a baseline cross‐sectional and 12‐month longitudinal audit 40 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One RCT was included, 22 and the remaining studies were observational. Of 22 observational studies, 18 reported the cross‐sectional prevalence of opioid use across various assessment periods 8,23–39 . One study combined a baseline cross‐sectional and 12‐month longitudinal audit 40 .…”
Section: Resultsmentioning
confidence: 99%
“…Three studies investigated period prevalence using a cohort design over 12 months, 41 24 months 42 and 41 months 43 . The majority of the included studies (18/23) were published in 2015 or later 8,22–27,29–32,34,35,38–41,43 . Data were sourced from South Australia, 8,24–27 New South Wales, 33,37,42 Victoria, 31,40 Queensland, 22 Tasmania 39 and Western Australia 30 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 By thoughtful evalu-ation of current practices, providers can identify valuable uses of CDS in countless workflows. 14 Our rounding reminder exemplifies a patient-specific relevant data display, one of the 53 types of front-end CDS tools defined by Wright et al in their CDS taxonomy. 15 This type of CDS can be highly effective, as prior work has shown that timely and welldesigned displays of salient information can assist with clinical task completion and make work easier for clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…52 The application of Internet of Things (IoT) technology has increased considerably, especially in vital sign monitoring. 53 Raban et al 54 reported that health care facilities can use EMRs as reminders to check and remove medication patches. Accordingly, LTS IS can be further integrated with EMRs or EHRs and connected with a main LTC system through a data exchange interface for relevant applications.…”
Section: Discussion and Future Workmentioning
confidence: 99%